Understanding the human factors contributing to highway accidents / Intan Syakila Haeizar and Asmalia Che Ahmad - Haeizar, Intan Syakila; Che Ahmad, Asmalia (2023)
Highways play a significant role in supporting economic growth and improving connectivity in Malaysia. However, highway accidents threaten public safety, making comprehending the factors contributing to their occurrence crucial. This article undertakes the human factors that contribute to highway accidents in Malaysia. A questionnaire survey method was employed, utilising quantitative analysis of factors influencing highway accidents. The sampling method utilised a simple random method with a sample size of 384 highway users in Malaysia. Six (6) factors influencing human behaviour were identified and examined to select the three (3) primary contributing factors in which the driver's recklessness ranks first among contributing factors. The findings provided insights into the primary contributors to highway accidents and will serve as a basis for developing suggestions and strategies to improve road safety. This research intends to help the development of proactive solutions to reduce accident rates and create safer transportation systems.